Children’s Spatial Play With a Block Building Touchscreen Application - Polinsky, Naomi; Lemley, Breniel; Flynn, Rachel M.; Wartella, Ellen; Uttal, David H. (Frontiers in Education, 2022)
Spatial play contributes to children’s early development of spatial skills, which are foundational for STEM achievement. A growing genre of spatial play for young children is digital block play. We asked how 3- to 6-year-old children (N = 115) engaged in digital block play and whether children’s age, gender, and spatial skills, were associated with this play. Children completed a spatial skills assessment and played a popular digital block play app, Toca Blocks. We developed a coding scheme that measured children’s play behaviors in the app, and reliably detected individual differences in this play. Children actively manipulated the digital blocks, and there were differences in their block play by age and gender. However, children’s spatial skills were not associated with their play in the app. The present work shows that digital block play supports play behaviors similar to those supported by physical blocks, but whether and how digital block play facilitates spatial learning is still unknown. The results are discussed in terms of potential ways to implement digital spatial play apps that might engage children’s spatial skills and support their spatial and STEM learning.